Predictors for the Development of Post-infection Irritable Bowel Syndrome after Acute Gastroenteritis: A Prospective Study - Agarwal, Rishabh; Prabhu, Madhav; Motimath, Pooja; Morkar, Dnyanesh; Patil, Rekha S. (Journal of Gastrointestinal Infections, 2025)
Post-infection irritable bowel syndrome (PI-IBS) is seen following an episode of acute gastroenteritis (AGE). Long-term studies have suggested that the risk of developing PI-IBS increases up to sixfold after gastrointestinal infection. This study aims to evaluate the incidence of PI-IBS and identify its risk factors.This prospective study was performed over a period of 1 year on AGE patients admitted to a tertiary care hospital in South India. Clinical and demographic characteristics were noted, and risk factors were evaluated. An IBS questionnaire ruled out ongoing or pre-existing IBS. The patients were followed up after 6 months to look for the development of IBS (Rome IV criteria).Out of 100 hospitalized AGE patients, one-fourth developed PI-IBS after 6 months. Out of them, 18 patients had the diarrhea-predominant (IBS-D) type, and the remaining 7 had the constipation-predominant (IBS-C) type. The factors that were significantly associated with PI-IBS were younger age, longer duration of AGE, depression, and abdominal cramps. On multivariate logistic regression analysis, longer duration of AGE (>7 days; p-value = 0.0040) and presence of abdominal cramps (p-value = 0.0130) were found to significantly influence the development of PI-IBS at 6 months.One-fourth of the patients in our study developed PI-IBS. Younger age, depression, longer duration of diarrhea, and abdominal cramps were statistically significant risk factors for the development of PI-IBS. Physicians should keep a high suspicion for PI-IBS in patients with such predisposing risk factors.
Keywords: bowel; Bristol; constipation; depression; diarrhea; gastroenteritis; infection; PI-IBS; Rome; stool